Lower survival and higher rates of cirrhosis in patients with ROUX-EN-Y gastric bypass hospitalised with alcohol-associated hepatitis. Issue 1 (20th February 2023) - Anugwom, Chimaobi; Thomson, Mary; Freese, Rebecca L; Lake, John R; Lim, Nicholas
Abstract : Objective: The incidence of alcohol-associated liver disease (ALD) is increasing, and weight loss surgery is more common due to the obesity epidemic. Roux-en-Y gastric bypass (RYGB) is associated with alcohol use disorder and ALD; however, its impact on outcomes in patients hospitalised for alcohol-associated hepatitis (AH) is unclear. Design: We performed a single-centre, retrospective study of patients with AH from June 2011 to December 2019. Primary exposure was the presence of RYGB. The primary outcome was inpatient mortality. Secondary outcomes included overall mortality, readmissions and cirrhosis progression. Results: 2634 patients with AH met the inclusion criteria; 153 patients had RYGB. Median age of the entire cohort was 47.3 years; median Model for End Stage Liver Disease - Sodium (MELD-Na) was 15.1 in the study group versus 10.9 in the control group. There was no difference in inpatient mortality between the two groups. On logistic regression, increased age, elevated body mass index, MELD-Na >20 and haemodialysis were all associated with higher inpatient mortality. RYGB status was associated with increased 30-day readmission (20.3% vs 11.7%, p<0.01), development of cirrhosis (37.5% vs 20.9%, p<0.01) and overall mortality (31.4% vs 24%, p=0.03). Conclusions: Patients with RYGB have higher rates of readmissions, cirrhosis and overall mortality after discharge from hospital for AH. Allocation of additional resources on discharge may improve clinical outcomes and reduce healthcare expenditure in this unique patient population.